Ginsenoside metabolite 20(S)-protopanaxatriol from Panax ginseng attenuates inflammation-mediated NLRP3 inflammasome activation. (6th April 2020) - Jiang, Jun; Sun, Xiao; Akther, Mahbuba; Lian, Mei-Lan; Quan, Lin-Hu; Koppula, Sushruta; Han, Jun-Hyuk; Kopalli, Spandana Rajendra; Kang, Tae-Bong; Lee, Kwang-Ho
Abstract: Ethnopharmacological relevance: Panax ginseng C.A. Meyer (Araliaceae), has been used in traditional medicine for preventive and therapeutic purposes in Asian countries. One of the active ginsenoside metabolites, 20( S )-Protopanaxatriol (PPT), has been associated with diverse pharmacological effects, including anti-inflammatory properties. Aim of the study: Although the capacity of PPT as an anti-inflammatory agent has been studied, this study aimed to explore the intrinsic mechanism of PPT in regulating inflammasome activation-mediated inflammatory responses in experimental models. Materials and methods: Lipopolysaccharide (LPS)-primed peritoneal macrophages in vitro was used to study the role of PPT on inflammasome activation. LPS-induced septic shock and monosodium urate (MSU)-induced murine peritonitis models were employed for in vivo evaluations. Results: PPT attenuated NLRP3 inflammasome activation and also reduced ASC oligomerization, leading to attenuation of interleukin (IL)-1β secretion. Further, PPT inhibited IL-1β secretion in both LPS-induced septic shock and MSU-induced mouse peritonitis models. Conclusions: This study revealed that ginsenoside metabolite PPT, inhibits inflammation-mediated inflammasome activation and supported the traditional use of ginseng in treating various inflammatory disorders. Graphical abstract: Image 1